Startup Culture Mindset A Primer to Building an Amazing Culture and Tribe - Schroeder, Bernhard (Gildan Media, 2020)
Startup Culture Mindset: A Primer to Building an Amazing Culture and Tribe was written for startup founders or executives who aspire to create an amazing team that buys into the mission. The key is to understand that the founder of a startup or leaders of a company determine the culture on purpose. And in order to do that well, you have to understand the key elements of a culture framework. Based on twenty years of company creation, leadership, and observation, Bernhard Schroeder shares with you the key elements of a culture framework: - Leadership: Led by the founders or key leaders of a startup. - Mission: The goal of the startup from a customer point of view. - Values: The core values of the startup, usually determined by the leadership. - Freedom/Accountability: The key mantra to any successful startup.
Vendor-supplied metadata
Keywords: Downloadable audio books; Audiobooks; Livres audio